Pengaruh Customer Satisfaction Terhadap Customer Loyalty Pada Produk Jahe Merah Lapas Khusus Gunung Sindur - Michael Dwi Putra; Padmono Wibowo (CV. KAMPUS AKADEMIK PUBLISING, 2023)
The aim of this article is to examine the effect of the customer satisfaction dimension on customer loyalty for the Merah Gunung Sindur product. This research is quantitative in nature from a study involving questionnaires distributed to 30 buyers from both cooperatives and re-sellers of Gunung Sindur red ginger. Research data were analyzed using SPSS 26, namely validity and reliability tests, normality tests, linearity tests, and simple linear regression tests. The key findings of this study reveal that respondents show an average of